2013
DOI: 10.1002/jbm.a.34799
|View full text |Cite
|
Sign up to set email alerts
|

Host response to microgel coatings on neural electrodes implanted in the brain

Abstract: The performance of neural electrodes implanted in the brain is often limited by host response in the surrounding brain tissue, including astrocytic scar formation, neuronal cell death, and inflammation around the implant. We applied conformal microgel coatings to silicon neural electrodes and examined host responses to microgel-coated and uncoated electrodes following implantation in the rat brain. In vitro analyses demonstrated significantly reduced astrocyte and microglia adhesion to microgel-coated electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…Here, reduced protein adsorption and inflammation are desired and current studies explore the applicability of microgel coated maBrought to you by | Carleton University OCUL Authenticated Download Date | 6/21/15 5:39 PM terials for this purpose [30]. Moreover, polyelectrolyte-mediated cross-linking of PNIPAM-co-AAc microgel films at Au coated substrates can resist large forces compared to their own mass and actuate in response to humidity [47].…”
Section: Biotechnical and Medical Applicationsmentioning
confidence: 97%
“…Here, reduced protein adsorption and inflammation are desired and current studies explore the applicability of microgel coated maBrought to you by | Carleton University OCUL Authenticated Download Date | 6/21/15 5:39 PM terials for this purpose [30]. Moreover, polyelectrolyte-mediated cross-linking of PNIPAM-co-AAc microgel films at Au coated substrates can resist large forces compared to their own mass and actuate in response to humidity [47].…”
Section: Biotechnical and Medical Applicationsmentioning
confidence: 97%
“…However, a number of in vivo studies looking at either stiff materials or those coated with compliant polymers have indicated that haptic-mediated mechanotransduction may not play as significant a role as initially thought (see Sections 4.1.3, 4.2.1, 4.3 and 4.6.1) . (117, 195) The second, and perhaps more predominant hypothesis, is that mechanical differences between the brain and microelectrodes induce adverse strains in the surrounding tissue during regular brain micromotion. (95, 138, 196) Therefore, compliant materials that have mechanical properties closer to that of brain tissue have received extensive attention towards improving microelectrode integration within the surrounding tissue.…”
Section: Materials Strategies For Improving Microelectrode Biocompamentioning
confidence: 99%
“…using conformal microgel coatings of poly(N-isopropylacrylamide) (pNIPAm) cross-linked with poly(ethylene glycol diacrylate) (PEG-DA) on silicon microelectrodes. (195) Long polyethylene glycol (PEG) chains take advantage of entropic and osmotic repulsion to prevent cell adhesion through the inhibition of protein adsorption. In vitro analyses demonstrated significantly reduced astrocyte and microglia adhesion to microgel-coated microelectrodes, compared to uncoated controls.…”
Section: Materials Strategies For Improving Microelectrode Biocompamentioning
confidence: 99%
“…No differences in glial and neuronal responses have been found between Parylene C and silicon dioxide surfaces, two commonly used insulation materials [33], and polyethylene glycol based hydrogel coatings did not shown benefit [36]. These results suggest that physical chemistry alone may not be sufficient to alter the host tissue response.…”
Section: Current Understanding Of Failure Mechanismsmentioning
confidence: 98%